Digital Marketing Strategies and Positioning of a Pharmacy in Lima, Peru - Alvarado-Mallqui, Chandra Naomi; Mateo-Salazar, Laydi Melissa; Rios-Lama, Cristian Armando; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
This research aimed to determine the relationship between digital marketing strategies and the positioning of a pharmacy in San Juan de Lurigancho, Lima, Peru, in 2022. The methodology employed was quantitative with a correlational level, and the sample consisted of 80 customers selected through non-probabilistic convenience sampling. The survey and two questionnaires were used as data collection tools. The results indicated a moderate correlation (r = 0.689) between digital marketing and positioning, with a significance level of = 0.000 < 0.05, rejecting the null hypothesis. In conclusion, digital marketing is significantly related to positioning, meaning that appropriately managing digital marketing strategies will increase or enhance the positioning of the pharmacy.